(untitled) - Kenney, Martin (New York, 1986)
The author raises important questions about whether the character of this university-industrial complex adequately allows for the kind of public discussion and participation necessary to insure consideration of social, economic, and moral issues in the development of this important new technology
Keywords: Biotechnology,Công nghệ sinh học